2006
DOI: 10.1007/s00403-006-0709-6
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the human epidermis in vitro: tools for basic and applied research

Abstract: Culture models of tissues and organs are valuable tools developed by basic research that help investigation of the body functions. Modelling is aimed at simplifying experimental procedures in order to better understand biological phenomena, and consequently, when suYciently characterized, culture models can also be utilized with high potential in applied research. In skin biology and pathology, the development of cultures of keratinocytes as monolayers has allowed the elucidation of most functional and structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(81 citation statements)
references
References 43 publications
3
73
0
5
Order By: Relevance
“…We therefore analyzed the regulation of AMP expression by these cytokines in vitro and in vivo. As expected, treatment of RHE, an in vitro model mimicking human skin (35), with IL-22 or IL-20 resulted in a strong upregulation of BD1, BD2, BD3, S100A7, S100A8, and S100A9 mRNA (Fig. 4A), which was confirmed at the protein level for BD2 (Fig.…”
Section: Il-22 and Il-20 Induce Amp Production By Reconstituted Epidesupporting
confidence: 81%
“…We therefore analyzed the regulation of AMP expression by these cytokines in vitro and in vivo. As expected, treatment of RHE, an in vitro model mimicking human skin (35), with IL-22 or IL-20 resulted in a strong upregulation of BD1, BD2, BD3, S100A7, S100A8, and S100A9 mRNA (Fig. 4A), which was confirmed at the protein level for BD2 (Fig.…”
Section: Il-22 and Il-20 Induce Amp Production By Reconstituted Epidesupporting
confidence: 81%
“…Other limitations of ex vivo absorption studies are as follows: i) The receptor fluid may influence the transfer of the Gene knock-down tissues, reporter tissues, wound models and models populated with various pathogens have also been described in the literature (Geer et al, 2004;Jansson et al, 1996;Kuchler et al, 2011;Popov et al, 2014;Poumay and Coquette, 2007;Zhai et al, 2007;van Drongelen et al, 2013). Reconstructed human skin models for therapeutic purposes (grafting) have additionally been described since the 1970s, several of which have been commercialized (Tab.…”
Section: General Introductionmentioning
confidence: 99%
“…Synthetic skin is a relatively new surrogate tissue that lends itself to investigation of a wide variety of processes while reducing the need for volunteer recruitment or laboratory animal testing (Poumay & Coquette, 2007). For extracting nucleic acids, we have found that synthetic skin is less susceptible to nucleic acid degradation and more easily homogenized than real human skin (data not shown).…”
Section: Skin Tissue Alternativesmentioning
confidence: 93%